Use of the consolidated framework for implementation research in a mixed methods evaluation of the EQUIPPED medication safety program in four academic health system emergency departments - Kegler, Michelle C.; Rana, Shaheen; Vandenberg, Ann E.; Hastings, S. Nicole; Hwang, Ula; Eucker, Stephanie A.; Vaughan, Camille P. (Frontiers in Health Services, 2022)
Background Enhancing Quality of Prescribing Practices for Older Adults Discharged from the Emergency Department (EQUIPPED) is an effective quality improvement program initially designed in the Veterans Administration (VA) health care system to reduce potentially inappropriate medication prescribing for adults aged 65 years and older. This study examined factors that influence implementation of EQUIPPED in EDs from four distinct, non-VA academic health systems using a convergent mixed methods design that operationalized the Consolidated Framework for Implementation Research (CFIR). Fidelity of delivery served as the primary implementation outcome. Materials and methods Four EDs implemented EQUIPPED sequentially from 2017 to 2021. Using program records, we scored each ED on a 12-point fidelity index calculated by adding the scores (1–3) for each of four components of the EQUIPPED program: provider receipt of didactic education, one-on-one academic detailing, monthly provider feedback reports, and use of order sets. We comparatively analyzed qualitative data from focus groups with each of the four implementation teams (n = 22) and data from CFIR-based surveys of ED providers (108/234, response rate of 46.2%) to identify CFIR constructs that distinguished EDs with higher vs. lower levels of implementation. Results Overall, three sites demonstrated higher levels of implementation (scoring 8–9 of 12) and one ED exhibited a lower level (scoring 5 of 12). Two constructs distinguished between levels of implementation as measured through both quantitative and qualitative approaches: patient needs and resources, and organizational culture. Implementation climate distinguished level of implementation in the qualitative analysis only. Networks and communication, and leadership engagement distinguished level of implementation in the quantitative analysis only. Discussion Using CFIR, we demonstrate how a range of factors influence a critical implementation outcome and build an evidence-based approach on how to prime an organizational setting, such as an academic health system ED, for successful implementation. Conclusion This study provides insights into implementation of evidence-informed programs targeting medication safety in ED settings and serves as a potential model for how to integrate theory-based qualitative and quantitative methods in implementation studies.